Patterns, evolution, and severity of striatal injury in insidious‐ vs acute‐onset glutaric aciduria type 1. Issue 1 (11th February 2019) - Boy, Nikolas; Garbade, Sven F.; Heringer, Jana; Seitz, Angelika; Kölker, Stefan; Harting, Inga
Abstract: Background: Striatal injury in patients with glutaric aciduria type 1 (GA1) results in a complex, predominantly dystonic, movement disorder. Onset may be acute following acute encephalopathic crisis (AEC) or insidious without apparent acute event. Methods: We analyzed clinical and striatal magnetic resonance imaging (MRI) findings in 21 symptomatic GA1 patients to investigate if insidious‐ and acute‐onset patients differed in timing, pattern of striatal injury, and outcome. Results: Eleven patients had acute and ten had insidious onset, two with later AEC (acute‐on‐insidious). The median onset of dystonia was 10 months in both groups, and severity was greater in patients after AEC ( n  = 8 severe, n  = 5 moderate) than in insidious onset ( n  = 4 mild, n  = 3 moderate, n  = 1 severe). Deviations from guideline‐recommended basic metabolic treatment were identified in six insidious‐onset patients. Striatal lesions were extensive in all acute‐onset patients and restricted to the dorsolateral putamen in eight of ten insidious‐onset patients. After AEC, the two acute‐on‐insidious patients had extensive striatal changes superimposed on pre‐existing dorsolateral putaminal lesions. Two insidious‐onset patients with progressive dystonia without overt AEC also had extensive striatal changes, one with sequential striatal injury revealed by diffusion‐weighted imaging. Insidious‐onset patients had a latency phase of 3.5 months to 6.5 years between detection and clinical manifestation of dorsolateral putaminal lesions. Conclusions: Insidious‐onset type GA1 is characterized by dorsolateral putaminal lesions, less severe dystonia, and an asymptomatic latency phase, despite already existing lesions. Initially normal MRI during the first months and deviations from guideline‐recommended treatment in a large proportion of insidious‐onset patients substantiate the protective effect of neonatally initiated treatment.